Study of Core Material Sandwich Panel In Ship Construction - Utomo, Edy; Zubaydi, Achmad; Pratisna, Pompy (IPTEK Journal of Proceedings Series, 2017)
AbstractÂ¾Sandwich panel in ship construction necessitates identification for the core material. Non-metal cores of sandwich materials were identifiedin this study for polyurethane foam, polyresin, and synthetic resin. This material identification was conducted through experiments using Det Norske Veritas (DNV) standard tests. The experiments conducted were reactivity test, density test, and tensile test. Results of the investigation show that the core material suitable for the sandwich panel is synthetic resin with composition of 50% resin,50% talc and 0.3% catalyst. The density of the material is 1,728 kg/m3, tensile strength is 24.75 Mpa, modulus of elastisity is 546.95 Mpa, and shear modulus is 273.48 Mpa.Â